2019
DOI: 10.1177/0306624x19845778
|View full text |Cite
|
Sign up to set email alerts
|

Women Released From Custody: Investigating Risk Factors and Reoffending

Abstract: This article draws on life-course and desistance theory to explore the relationship between the factors of age, ethnicity, offence type, and incarceration history for a sample of 1,035 women released from custody between January 2013 and January 2014, data gathered from the Australian Queensland Corrective Services administrative dataset. It also explores their impact on recidivism and the time between release and reoffending (known as “time to failure”) until September 2017. The data indicate substantial rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…RTC group women were significantly younger; with higher proportions identifying as Aboriginal or Torres Strait Islander, having lower educational attainment and limited work experience compared to no-RTC group women. These findings are consistent with existing research that has found younger age, low educational attainment, unemployment and being a First Nations person or person from a culturally and linguistically diverse community to be correlated with recidivism [ 71 75 ].…”
Section: Discussionsupporting
confidence: 92%
“…RTC group women were significantly younger; with higher proportions identifying as Aboriginal or Torres Strait Islander, having lower educational attainment and limited work experience compared to no-RTC group women. These findings are consistent with existing research that has found younger age, low educational attainment, unemployment and being a First Nations person or person from a culturally and linguistically diverse community to be correlated with recidivism [ 71 75 ].…”
Section: Discussionsupporting
confidence: 92%
“…Women have specific reproductive health needs in relation to pregnancy and childbirth (Bard et al, 2016 ) and have a high risk of returning to custody. A recent study in Queensland found that 70% women returned to custody within 2–4 years after release with 50% returning to custody within 1 year (De Rooy et al, 2019 ). Risk factors for re-offending included violent offenses, longer incarceration, younger age and identifying as Indigenous (De Rooy et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in Queensland found that 70% women returned to custody within 2–4 years after release with 50% returning to custody within 1 year (De Rooy et al, 2019 ). Risk factors for re-offending included violent offenses, longer incarceration, younger age and identifying as Indigenous (De Rooy et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there is an increasing need to address the sexual health and safety of women on probation. Over 70% of women are rearrested and return to jail for technical violations within their first three years on probation (De Rooy et al, 2019 ). Some recurrent arrests appear to be related to limited access to community-based health services that can be somewhat more easily accessed while incarcerated (De Rooy et al, 2019 ; Sawyer, 2019 ).…”
Section: Introductionmentioning
confidence: 99%